Koli woman preparing a dish - Mumbai Archive Project Team (Jio Institute, 2024)
Pictured here is a Koli woman preparing a dish known as a sweet banana. Making this involves peeling a ripe banana, delicately slicing it to stuff with coconut filling and then gently roasting it in butter.